Ecological Conditions and Molecular Determinants Involved in Agrobacterium Lifestyle in Tumors - Meyer, Thibault; Thiour-Mauprivez, Clémence; Wisniewski-Dyé, Florence; Kerzaon, Isabelle; Comte, Gilles; Vial, Ludovic; Lavire, Céline (Frontiers in Plant Science, 2019)
The study of pathogenic agents in their natural niches allows for a better understanding of disease persistence and dissemination. Bacteria belonging to the Agrobacterium genus are soil-borne and can colonize the rhizosphere. These bacteria are also well known as phytopathogens as they can cause tumors (crown-gall disease) by transferring a DNA region (T-DNA) into a wide range of plants. Most reviews on Agrobacterium are focused on virulence determinants, T-DNA integration, bacterial and plant factors influencing the efficiency of genetic transformation. Recent research papers have focused on the plant tumor environment on the one hand, and genetic traits potentially involved in bacterium-plant interactions on the other hand. The present review gathers current knowledge about the special conditions encountered in the tumor environment along with the Agrobacterium genetic determinants putatively involved in bacterial persistence inside a tumor. By integrating recent metabolomic and transcriptomic studies, we describe how tumors develop and how Agrobacterium can maintain itself in this nutrient-rich but stressful and competitive environment.